AN ISLAMIC PERSPECTIVE ON E-SPORT COMPETITION - Bangkit Wira Malik; Harisah, Harisah (Islamuna: Jurnal Studi Islam, 2024)
ABSTRACTThis paper focuses on the study of a phenomenon that has just emerged due to the rapid development of technology, namely the e-sport competition which is much favored by millennials. The purpose of this study is to analyze how the law of e-sport competition is viewed from the arguments of the Al-Qur'an and Hadits, and how the law of the professional player profession, as well as maqashid sharia stipulation of a law. This research is a type of qualitative research whose data sources come from primary data sources through direct interviews with one of the professional players, and secondary data sources through studies of various literature such as books, articles in journals, and others. The results of this study indicate that: First, e-sport competitions are included in prize competitions that are forbidden in Islam because they have violated all the provisions contained in the Al-Qur'an and Hadith. Second, with the prohibition of e-sport competition, it will have implications for the law of the professional player profession which causes it to become an unlawful profession. Third maqashid sharia regarding the determination of a law is to protect and maintain the needs that are essential for humans, namely: religion, soul, mind, offspring, and property. So that this research makes an important contribution to the development of contemporary fiqh and Islamic law studies that are relevant to new phenomena in the digital era related to e-sport competitions.ABSTRAKTulisan ini berfokus pada kajian mengenai fenomena yang baru muncul akibat pesatnya perkembangan teknologi yaitu tentang kompetisi e-sport yang banyak digemari oleh kalangan milenial. Tujuan penelitian ini adalah untuk menganalisis bagaimana hukum kompetisi e-sport  ditinjau dari dalil Al-Qur’an dan Hadits, dan bagaimana hukum profesi professional player, serta maqashid shariah penetapan suatu hukum. Penelitian ini merupakan jenis penelitian kualitatif yang sumber datanya berasal dari sumber data primer malalui wawancara secara langsung kepada salah satu professional player, dan sumber data sekunder melalui kajian dari berbagai literatur seperti buku, artikel dalam jurnal, dan lain-lain. Hasil dari penelitian ini menunjukkan bahwa: Pertama, kompetisi e-sport termasuk ke dalam kompetisi berhadiah yang diharamkan dalam Islam karena telah melanggar semua ketentuan yang terdapat dalam Al-Qur’an dan Hadits. Kedua, dengan diharamkannya kompetisi e-sport maka akan berimplikasi kepada hukum profesi professional player yang menyebabkannya menjadi profesi yang bathil. Ketiga maqashid shariahmengenai penetapan suatu hukum adalah untuk menjaga dan memelihara kebutuhan yang sifat nya esensial bagi manusia yaitu: agama, jiwa, akal, keturunan, beserta harta. Sehingga penelitian ini memberikan kontribusi penting terhadap pengembangan kajian fikih dan hukum Islam kontemporer yang relevan dengan fenomena baru di era digital terkait kompetisi e-sport.